2020
DOI: 10.3389/fendo.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

Both JNK1 and JNK2 Are Indispensable for Sensitized Extracellular Matrix Mineralization in IKKβ-Deficient Osteoblasts

Abstract: Extracellular matrix mineralization is critical for osteogenesis, and its dysregulation could result in osteoporosis and vascular calcification. IKK/NF-κB activation inhibits differentiation of osteoblasts, and reduces extracellular matrix mineralization, however the underlying mechanisms are poorly understood. In this study, we used CRISPR/Cas9 system to permanently inactivate IKKβ in preosteoblast cells and confirmed that such cells displayed dramatic increase in extracellular matrix mineralization associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In a previous study, optimized ECM could induce stronger osteogenic effects in mesenchymal stem cells ( Freeman et al, 2019 ). In another recent study, it was reported that ECM mineralization was critical for osteogenesis, and its dysregulation could result in osteoporosis ( Hao et al, 2020 ). The results of the current study are concordant with those previous results.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, optimized ECM could induce stronger osteogenic effects in mesenchymal stem cells ( Freeman et al, 2019 ). In another recent study, it was reported that ECM mineralization was critical for osteogenesis, and its dysregulation could result in osteoporosis ( Hao et al, 2020 ). The results of the current study are concordant with those previous results.…”
Section: Discussionmentioning
confidence: 99%
“…DHA can increase the expression of CASP3 during LPS-induced osteoclastogenesis [13]. MAPK8 can regulate osteoblast autophagy and mitophagy, promoting extracellular matrix mineralization [27][28][29]. Therefore, EGFR, CASP3, and MAPK8 were focused on the next experiments exploring the anti-OP mechanism of ARS and its derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the cells were washed with distilled water three times to eliminate nonspecific staining. To quantify extracellular matrix mineralization, the bound stain was eluted with 10% (w/v) cetylpyridinium chloride (Sigma-Aldrich, St. Louis, MO, USA) in water at room temperature for 40 min followed by dilution with the same volume of 10% (w/v) cetylpyridinium chloride [ 18 ] and then quantified by measuring absorbance at 570 nm.…”
Section: Materials and Methodsmentioning
confidence: 99%